Sustainability Assessment of Malaysian Palm Oil Industry - Lim, Chye Ing (Curtin University, 2019)
The Palm Oil Sustainability Assessment framework has been developed to improve sustainability performance of Malaysian palm oil production. It was applied to a crude palm oil supply chain to identify sustainability improvement strategies. A biogas plant has been incorporated into the existing supply chain to improve the sustainability performance of crude palm oil production. This framework will assist stakeholders in the supply chain to select appropriate strategies for sustainable palm oil production.